2021
DOI: 10.1029/2021av000431
|View full text |Cite
|
Sign up to set email alerts
|

Widespread Mismatch Between Phenology and Climate in Human‐Dominated Landscapes

Abstract: Phenology, the timing of recurring biological events, is nature's calendar, and changes in vegetation phenology are known to be among the most sensitive responses to ongoing climate change (Parmesan & Yohe, 2003). Evidence clearly shows warming-driven shifts in vegetation phenology at the global scale, such as earlier greenup and later senescence (

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 80 publications
0
4
0
Order By: Relevance
“…The response of vegetation phenology to climate changes has regional differences. Vegetation in mid-to-high latitudes (between 30-70 • N) is particularly sensitive to climate changes [25]. We are therefore interested in the boundary of the area between latitudes between 30-70 • N within the ecoregions of North America and with coverage of deciduous forests.…”
Section: Study Areamentioning
confidence: 99%
“…The response of vegetation phenology to climate changes has regional differences. Vegetation in mid-to-high latitudes (between 30-70 • N) is particularly sensitive to climate changes [25]. We are therefore interested in the boundary of the area between latitudes between 30-70 • N within the ecoregions of North America and with coverage of deciduous forests.…”
Section: Study Areamentioning
confidence: 99%
“…Intensity–frequency structure of precipitation and its changes under global warming impact the local hydrological cycle, which is of significant importance to biodiversity conservation and risk evasion (Rietkerk et al, 2021; Song et al, 2021; Trenberth et al, 2003). The diurnal cycle of intensity–frequency structure of precipitation over the SETP and surroundings revealed by this method is conductive to ecomanagement and water resource management there.…”
Section: Discussionmentioning
confidence: 99%
“…The first is that the impacts of warming temperatures are not yet great enough to induce a full shift of a migration run which is also constrained by photoperiod (Durif et al, 2005) and moon phase (Sandlund et al, 2017). Secondly, where species are not able to track changes in environmental conditions fast enough to allow timely adaptation (Reed et al, 2011), changes in phenology may lag behind the rates observed in climate variables, resulting in a mismatch that can be ecologically detrimental (Bertrand et al, 2011;Strangeways, 2018;Arevalo et al, 2021a;Song et al, 2021). This is especially true for long-lived species with consequential slow generational turnover, such as European eel.…”
Section: Discussionmentioning
confidence: 99%